Peningkatan Hasil Belajar PAKBP Materi Sepuluh Perintah Allah Dengan Metode PBL Kelas IV SD Negeri 14 Huta Hotang: (Problem Basic Learning) - Magdalena Silva Fiskayanti Samosir; Andarweni Astuti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study aims to improve the learning outcomes of fourth-grade students at SD Negeri 14 Huta Hotang in the subject of Catholic Religious Education and Character, specifically focusing on the topic